ANALISIS PENGENDALIAN PERSEDIAAN DENGAN METODE EOQ USAHA STAN KAYU SINAR SOWI KABUPATEN MANOKWARI - Rizkyani Pratama; Yulius H Saptomo; Dirarini Sudarwadi (Cakrawala Management Business Journal, 2019)
Controlling and determining of inventory is an important thing in order to produce efficiently and able to make smooth sales. The purpose of this research is to know an analysis of controlling raw material inventoriesin the manufacture of brick by using Economic Order Quantity (EOQ) method to increase efficiency of the total inventory costin Stan Kayu Sinar Sowi. The raw material of brick is rough sand and cements. Type of case study research through a qualitative approach by means of interviews, observation and documentation. Case study on a wood booth business in Manokwari, West Papua. The results of the study that the purchase of raw materials made by the company is considered less efficient, because company policies tend to cause expenditure to be greater in the amount of Rp.606,620,250 for 12 months (1 period), while using the Economic Order Quantity (EOQ) method will issue a fee of Rp.550,712,500 for the same period. Using the Economic Order Quantity (EOQ) method, the order quantity is higher and the order frequency will be lower, resulting in order cost savings and increasing the total inventory cost efficiency.